2010
DOI: 10.1016/j.ejcts.2009.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal lacerations after endotracheal intubation: a proposed morphological classification to guide non-surgical treatment☆☆☆

Abstract: Level I or II PITL should be managed non-surgically. When adequate respiratory status is present, Level IIIA PITL can be managed conservatively in selected institutions only, because these injuries are high-risk injuries. Any PITL associated with injury involving the oesophagus or with mediastinitis (Level IIIB) must be treated as soon as possible by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
128
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 19 publications
1
128
0
10
Order By: Relevance
“…Cardillo et al 6) reported that lesions are classified into four types depending on the depth of the tracheal injury: Level I includes injuries with mucosal or submucosal tracheal involvement without mediastinal emphysema and without esophageal injury; level II includes tracheal lesions up to the muscular wall with subcutaneous or mediastinal emphysema but without esophageal injury or mediastinitis; level IIIA is a complete laceration of the tracheal wall with an esophageal or mediastinal soft-tissue hernia but without esophageal injury or mediastinitis; and level IIIB is any laceration of the tracheal wall with an esophageal injury or mediastinitis. 6) The authors reported no mortalities and postulated that conservative treatment was possible even with a complete laceration of the tracheal wall if no esophageal injury or mediastinitis was present (level IIIA). We disagree with his opinion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardillo et al 6) reported that lesions are classified into four types depending on the depth of the tracheal injury: Level I includes injuries with mucosal or submucosal tracheal involvement without mediastinal emphysema and without esophageal injury; level II includes tracheal lesions up to the muscular wall with subcutaneous or mediastinal emphysema but without esophageal injury or mediastinitis; level IIIA is a complete laceration of the tracheal wall with an esophageal or mediastinal soft-tissue hernia but without esophageal injury or mediastinitis; and level IIIB is any laceration of the tracheal wall with an esophageal injury or mediastinitis. 6) The authors reported no mortalities and postulated that conservative treatment was possible even with a complete laceration of the tracheal wall if no esophageal injury or mediastinitis was present (level IIIA). We disagree with his opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the indications for conservative treatment are as follows: 1) stable vital signs, 2) spontaneous ventilation, 3) absence of esophageal injury, 4) non-progressive pneumomediastinum with/without subcutaneous emphysema, and 5) no signs of sepsis. [1][2][3][4][5][6] Surgical repair is highly recommended under some clinical situations. First, a tracheal injury of >2 cm should be treated surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, technical errors, including intubation by force, inexperienced hands, inappropriate tube size, over distended cuff. Second, factors related to the patient condition, consist of tracheal anomalies, old age patients, chronic corticosteroid therapy, short stature, female sex and COPD [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommend surgery while others do not definitely exclude endoscopic treatment giving a greater attention to the depth of the tracheal injury than to its length (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Recently, Cardillo et al (12) classified PITL into four levels according to the depth of the tracheal fear and proposed a protocol for its management. Level I: laceration of mucosa and submucosa with subcutaneous or mediastinal emphysema; Level II: tracheal lesion up to the muscularis wall without mediastinal emphysema and without oesophageal injury; Level III-A: complete laceration of the tracheal wall with oesophageal or mediastinal soft-tissue hernia without oesophageal injury or mediastinitis; and Level IIIB: any laceration of tracheal wall with oesophageal injury or mediastinitis.…”
Section: Introductionmentioning
confidence: 99%